Waste paper as a music source: fragments preserved with the incunabula at the University Library in Wroclaw - Gancarczyk, Paweł (Interdisciplinary Studies in Musicology, 2018)
Preserved with the incunabula at the University Library in Wroclaw are eighty-five fragments of music manuscripts. Alongside numerous antiphonaries, notated breviaries and missals, they also include a fragment with polyphonic music (PL-WRu XV Q1066). This contains three compositions typical of fifteenth-century Central European repertory. There are grounds for supposing that this fragment was written in Silesia during the second quarter of that century. Research into the music fragments from the University Library in Wroclaw has provided the author with a point of departure for discussing methodological issues. Questions are raised regarding the nature of fragmentary sources, with reference to the classification of historical sources proposed by Jerzy Topolski. The status of fragments differs from that of sources preserved intact, and this should be reflected in research procedures, such as the method of establishing provenance. The adoption of new methodological principles requires a critical re-examination of the interpretation of some musical fragments, including the sources preserved in Poland.